2021
DOI: 10.1002/jnr.24947
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of specific spatial functional connectivity difference in depression during sleep

Abstract: The connectivity of the brain network allows the brain to perform a variety of complex functions (Friston, 2011). Functional connectivity (FC) represents the temporal correlations that suggest direct or indirect interactions between brain regions (Friston et al., 1993;Song et al., 2008). Studying FC and dynamics in neural networks allows us to understand how the brain performs various complex functions (He et al., 2019). It has also been reported that the brain network connectivity is affected by mental illnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…It has also been reported that patients had less gray matter volume in the right hemisphere and greater gray matter volume in the left hemisphere than the healthy controls ( Peng et al, 2019 ). Our previous research also found some evidence of cortical lateralization in patients ( Lian et al, 2021 ). In addition, transcranial magnetic stimulation over the separate hemisphere can alleviate the imbalance between the hemispheres and effectively improve the patients’ core depression factors and anxiety symptoms ( O'Reardon et al, 2007 ; Carpenter et al, 2017 ; Cristancho et al, 2019 ; Li C.-T. et al, 2020 ; Wang et al, 2022 ).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It has also been reported that patients had less gray matter volume in the right hemisphere and greater gray matter volume in the left hemisphere than the healthy controls ( Peng et al, 2019 ). Our previous research also found some evidence of cortical lateralization in patients ( Lian et al, 2021 ). In addition, transcranial magnetic stimulation over the separate hemisphere can alleviate the imbalance between the hemispheres and effectively improve the patients’ core depression factors and anxiety symptoms ( O'Reardon et al, 2007 ; Carpenter et al, 2017 ; Cristancho et al, 2019 ; Li C.-T. et al, 2020 ; Wang et al, 2022 ).…”
Section: Discussionsupporting
confidence: 62%
“…Based on the synchronous likelihood method, the global synchronization of depressed patients has been confirmed to be lower in the δ, θ, and σ bands in the sleep state ( Leistedt et al, 2009 ; Hasanzadeh et al, 2020 ). In addition, the recent study in our group successfully applied sleep electroencephalography (EEG) functional connectivity to detect depressed patients, and the obtained results were delightful ( Lian et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The participants reported that the air mattress was softer than the control mattress. Our previous studies indicated that MDD patients showed a consistent enhancement of functional connectivity (Lian et al, 2021;Song et al, 2022;Zhang et al, 2022b), and the female participants exhibited stronger EEG functional connectivity than the male participants (Liao et al, 2019). We are aware that female patients are more likely to suffer from depression (Eid et al, 2019;Gao et al, 2020b) and that patients with depression are more sensitive to the outside environment.…”
Section: Figurementioning
confidence: 96%